THE ANALYSIS OF PROBLEM BASED LEARNING MODEL ON CREATIVITY STUDENT OF HIGH SCHOOL PHYSICS - Irawati Lebora Hutabarat; Nurdin Bukit (Jurnal Pendidikan Fisika, 2018)
This study aims to analyze the creativity of physics learning students who taught with problem-based learning with direct learning. This research is a quasi experimental research with two group pretest posttest design. The population of this study is all students of class X SMA Negeri 2 Bandar semester II academic year 2016/2017. The sample of this research was taken by clus random sampling that is as much as 2 classes which amounted to 64 students, experiment class consisting of 32 students applied with problem based learning and control class consist of 32 students applied by direct learning. The instrument used in this research is the creativity test instrument in the form of a description of 7 problems that have been declared valid by the team of experts. The resulting data is analyzed by t test is the test of creativity hypothesis is t count > ttable (6,124> 1,988) hence can concluded student physics creativity which d taught with problem based learning model better than student which is taught by direct